Day 1 Wed, April 20, 2016 2016
DOI: 10.2118/180007-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cuttings Transport Modeling - Part 1: Specification of Benchmark Parameters with a Norwegian Continental Shelf Perspective

Abstract: In oil and gas drilling, cuttings transport related problems are a major contributor to well downtime and costs. As a result, solutions to these problems have been extensively researched over the years, both experimentally and through simulation. Numerous review articles exist, summarizing not only the research history but also the qualitative effect of individual case parameters such as e.g. pump flow rate, pipe rotation, rate of penetration on cuttings transport. However, comparing different studies is chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…35,58 A further complication that limits the holistic automation of drilling systems is that several independent software solutions exist that address the different aspects of the drilling operation in isolation. 9,91 Integrating all solutions within a single control framework is not a trivial task. In order to address this challenge, a control hierarchy design for production optimisation by Saputelli et al 92 was adapted to drilling automation operations.…”
Section: Control and Automation Of Managed Pressure Drillingmentioning
confidence: 99%
See 1 more Smart Citation
“…35,58 A further complication that limits the holistic automation of drilling systems is that several independent software solutions exist that address the different aspects of the drilling operation in isolation. 9,91 Integrating all solutions within a single control framework is not a trivial task. In order to address this challenge, a control hierarchy design for production optimisation by Saputelli et al 92 was adapted to drilling automation operations.…”
Section: Control and Automation Of Managed Pressure Drillingmentioning
confidence: 99%
“…The scarcity of the cuttings inlet velocity is a factor that limits experimental validation of CFD models. Busch et al 91 presented a benchmarking procedure for cuttings transport studies and provided a set of parameters that must be reported in experimental and modelling studies. It is expected that such procedures will enhance industrial applicability of developed models and the accompanying findings/results.…”
Section: Application Of Cfdmentioning
confidence: 99%
“…They validated their model against ECD field data obtained during LWD operations. For a more thorough review on the modelling of cuttings transport using CFD, the interested reader is referred to (Nazari et al;2010;Kelin et al, 2013;Demiralp, 2014;Amanna et al, 2015;Epelle and Gerogiorgis, 2017;Manjula et al, 2017;Movreji et al, 207;Epelle and Gerogiorgis, 2018;Busch et al, 2018).…”
Section: Related Literaturementioning
confidence: 99%
“…As a result of the field-sensitive nature and the peculiarities of the challenges associated with in various practical drilling operations, generalising research findings can be tricky (Busch et al, 2018;Hakim et al, 2018;Yeu et al, 2019). However, some of the common unresolved questions that influence the decisions of all drilling engineers include: what mud viscosity should be used/what are the most favourable mud properties; what is the acceptable trade-off between the mud weight and its circulating velocity; how high should the fluid velocity be to avoid cuttings buildup; how does the annular clearance affect annular pressure drop (Epelle and Gerogiorgis, 2017;Katende et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate cutting transport is associated with many problems such as lowering the drilling performance, grinding of cuttings into fines at bit, difficulties in mud and solid control maintenance, increasing the equivalent circulating density (ECD), increasing the mechanical torque and drag, over pull on drilling string and unnecessary back reaming and fishing operation. 1,2,3 Therefore, the bottom hole has been a concern for drilling operations which is resulted in excessive well construction expenditure. 4 Bottom Hole Assembly (BHA), drill pipe rotary speed (RPM), flow rate, rate of penetration (ROP) and drilling fluid properties and inclination are the common factors that can be manipulated and controlled to gain a proper hole .…”
Section: Introductionmentioning
confidence: 99%